Application of the Case Teaching Method in a Pharmaceutical Analysis Online Course - Ni, Dan-Rong; Gong, Li-Hong; Jin, Chun-Hua; Li, Wen-Chao; Li, Hai-Yan (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: To explore the teaching effect of integrating the case teaching method into an online course on pharmaceutical analysis. Materials and Methods: The case teaching method was adopted as the technique for delivering professional knowledge. The online course integrated knowledge teaching, practical ability, and value guidance. The effect of the case teaching method was evaluated by course assessment and a questionnaire. Results: After the reform, students’ online course examination scores were greatly improved. The "excellent" or "good" rate increased from 7.7% to 53.8%, and 96.2% of students thought they had fully achieved their teaching objectives with high satisfaction. Conclusion: The integration of the case teaching method into the pharmaceutical analysis online course improved its teaching quality; therefore, it is worth promoting and applying in the future.
Keywords: Case teaching method; Drug analysis; Online courses